Objectiver le dire sur la pratique : quels apports de Bourdieu à l’analyse de pratiques enseignantes ? - Béatrice Pudelko (Éducation et Socialisation)
For two decades, education sciences in the French-speaking world have seen the number of analytical research processes concerning actual teaching practices that use various verbalization methods multiply. These methods are based on the principle of “primacy of intrinsic description of action”, according to which the meaning of an action can only be determined by the person who is carrying it out, in a configuration that always remains dialogical between practitioner and researcher. Data objectivization requirements of first-person accounts are found throughout Pierre Bourdieu’s practice theory because they influence the possibility of constructing a theoretical model of practice that respects its subjective aspect, which is both physically and temporally bound. This paper analyzes (i) the main issues and problems encountered by Bourdieu in doing so and (ii) the potential contribution of his theory to the objectivization of this type of research actions in the field of teaching practice analysis.